Pengaruh Penilaian Produk, Harga dan Promosi Online terhadap Keputusan Pembelian pada PT. Lazada Indonesia - Aries Kasman; Aminar Sutra Dewi (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The objective of this research is to objectively determine how customers of PT. Lazada Indonesia influences their decisions to buy goods through pricing, prices and online promotions. According to the terms posted by Lazada Marketpalace users, participants in the study had to be at least eighteen years old, and the study used a non-conjectural sampling method. To collect data, a questionnaire was used. To test the hypothesis, validity, descriptive analysis, classical hypothesis, Linear regression analysis, and T Test. The research results show that various components, including product quality, price, and online promotions, greatly influence purchase satisfaction.